Wearable sensor technology to predict core body temperature: a systematic review - Dolson, C.; Harlow, E.; Calcei, J.; Voos, J.; Seshadri, D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Exertional heat-related illness (HRI) is increasing in incidence as global temperatures rise, with heat-related deaths increasing by 74% globally from 1980 to 2016[1]. Despite the frequency and potentially fatal consequences of undetected HRI, coaches, trainers, supervisors, and employers currently rely on visible cues and subjective assessments of their athletes and employees for early detection, such as malaise, confusion, thirst, ataxia, or excessive sweating. The measurement of core body temperature (CBT) using existing rectal, esophageal, or pill thermometers has been shown to predict HRI and its severity, but these measurement methods are excessively invasive, obstructive, or costly for high acuity and high motion settings. Noninvasive prediction of CBT using wearable technology and predictive algorithms offers the potential for continuous CBT monitoring and early intervention to prevent HRI in athletic, military, and intense work environments. 1. Fernandez, M. Extreme Heat-Caused Deaths Have Jumped 74% in the Last 30 Years Available online: https://www.axios.com/2021/08/20/extreme-heat-killed-nearly-400000-people-globally (accessed on 1 December 2022).